Pattern Recognition using Modified Compression Algorithm with Mexican Hat (MCAMH) - Upadhyay, Rishav; Biswas, Prasenjit; Poddar, Partha Protim; Mandal, Rakesh Kumar (International Journal of Computer Sciences and Engineering, 2015)
Making a machine understand and recognize a character is a challenge. This is also factored as many researchers have indulged in building worthy hardware and necessary software for character recognition. A well known tool to solve this problem is Artificial Neural Network (ANN). In this paper, Mexican Hat, a fixed-weight net, is used to improve the precision than the previous attempts which already have been introduced. Here 14 X 14 image matrices have been taken as input and then compressed into 7 X 7 matrices, reducing the elements which are of no or little significance. Mexican Hat is used to recognize the alphabet.